The Influence of The Ethnocentrism Paradox on Super Priority Tourism Development in Indonesia - Muhammad Ade Kurnia Harahap; Rosalina Andriyani Ebang Pareira; Musran Munizu; Yudha Adytya Pertywy; Heppi Syofya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine (1) the paradoxical influence of ethnocentrism in fostering multicultural identity as an attraction for super priority destinations; and (2) the paradoxical influence of ethnocentrism increases local tourists' interest in visiting super priority destinations. This research is qualitative-descriptive research. The results of this research show that (1) the ethnocentrism paradox has a positive influence on the development of super-priority tourism through multicultural identity, the government can take advantage of a society's ethnocentrism attitude at the right level to introduce local culture and customs, through tourist visits to local residential areas which generally still maintain tribal customs or through performances that introduce local regional arts in super priority destination areas in Indonesia; and (2) the paradox of ethnocentrism has a positive effect on local tourists' interest in traveling to super-priority destinations, tourists who have a high ethnocentrism attitude become more concerned about the existence of super priority destinations as domestic tourism.